The Theme of Emigration and Exile in Galician Drama: Some Cases - Pascual Rodríguez, Roberto (Madrygal. Revista de Estudios Gallegos, 2015)
In this article we draw an analytical and comparative discourse in Galician dramatic literature in which the conflict of emigration is seen as a tragic constant, from Anton Villar Ponte´s works to those of Roberto Salgueiro, Cándido Pazó, Daniel Cortezón, etc.
Keywords: Emigration; Galician theatre; Irmandades da Fala; new Galician dramaturgy